Enhanced nitrogen removal via simultaneous nitrification and denitrification by a newly isolated strain Enterobacter cloacae GW6 from estuarine sediment - Shufeng Chen; Zhicai Zhang; Yinhua Wang; Chunping Wang; Xin Zhang; Xu Wang; Yalin Wu; Yidong Wang; Hongyu Guo (PLoS ONE, 2026)
Excessive nitrogen has been discharged into natural environments due to anthropogenic activities, leading to numerous negative impacts on natural ecosystems worldwide and becoming a global environmental issue. Therefore, effective removal of nitrogenous contaminants from natural ecosystems is crucial for the protection of both ecological sustainability and human interests. In this study, a strain of Enterobacter cloacae GW6 was newly isolated from natural estuarine sediment. This strain could utilize ammonium, nitrite and nitrate, with removal efficiencies of 99.60%, 93.73% and 98.79%, and the maximum removal rates of 39.96, 40.39 and 44.65 mg/L/h, respectively. Importantly, Strain GW6 showed excellent simultaneous heterotrophic nitrification and aerobic denitrification (HN-AD) capability with the maximum TN removal rate of 35.27 mg/L/h, which is greater than those of many other HN-AD bacteria reported previously, indicating that Strain GW6 was suitable for the efficient nitrogen removal in aquatic ecosystems with high ammonium, nitrite and nitrate concentrations. The detection of functional genes amoA , hao , napA , nirK and nosZ from Strain GW6 further confirmed its HN-AD capability. Strain GW6 exhibited strong nitrogen removal capability across a wide range of environmental conditions, which makes it a promising candidate as a HN-AD bacterium for the effective biological treatment of nitrogen contamination and eutrophication in natural aquatic ecosystems, thereby contributing to better environmental protection.